156. Dosimetric comparison between 3D-CRT, Field in Field and VMAT techniques in the adjuvant radiotherapy treatment of breast cancer. (December 2018) - De Nile, M.C.; Perna, L.; Mangili, P.; Signorotto, P.; Longobardi, B.; Cattaneo, G.M.
Abstract : Purpose: To compare 3D-CRT, Field-in-Field (FIF) and VMAT for adjuvant radiotherapy of breast cancer. Methods: 26 patients (13 with left-sided breast cancer, 13 with right-sided) treated to a prescribed dose of 40 Gy (2.667 Gy/fraction; normalized to the target mean) were considered. For all patients a 3D-CRT and a VMAT plan were simulated. 3D-CRTs were planned with 2 primary tangential fields with physical wedges and 2 additional low weighted segments. VMAT plans were performed with a Rapid Arc (RA) technique using 2 partial arc. In a subgroup of 15 patients FIF technique was implemented, combining two open fields with 2–3 segments in two tangential beam directions, without using wedges. Comparisons were performed in terms of PTV coverage and OARs dose-volume histogram (DVH) parameters, considering optimal/acceptable constraints of RTOG-1005 protocol. The dosimetric value of omolateral (lung/heart) OARs were related to the OARs volume included in the chest concavity and to OAR's inclusion maximum depth. Results: Concerning PTV, coverage was similar for the three techniques. The mean dose to OARs are summarized in the table. RA was sub-optimal for all contralateral OARs because mean doses were significantly (p < 0.05) higher compared with 3D-CRT (FIF): +1.8 Gy (+2.0 Gy) breast; +1.8 Gy (+2.2 Gy) lung and +2.0 Gy (+2.4 Gy) heart. FIF gave better results in term of omolateral OARs constraints when the maximum depth was lower than 1/1.5 cm for lung and heart (left patients, Figure); after this value RA was the best technique. The optimal RTOG-1005 constraints were satisfied in 62.0%, 80.3%, 59.7% for 3D-CRT, FIF e RA respectively. Conclusions: The FIF (3D-CRT) technique is similar to RA for PTV data and presents the best results all contralateral OARs. Only when (omolateral) lung and heart have an inclusion in chest concavity >1.5 cm, RA significantly reduces dose in the high DVH region.